IMPLEMENTATION OF HUMAN RESOURCE (SDM) MANAGEMENT IN THE 4.0 INDUSTRIAL REVOLUTION ERA AT SD INTIS SCHOOL YOGYAKARTA - Habibi, Adib; Arifin, Zainal; Khusnuridlo, Moh (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2023)
A predominance of school with good infrastructure, excellent services, and standardized facilities is backgrounding this study. The school had applied contract-based teacher system far before it was legalized. A systematic and structured system, however, eliminates and fades the teachers’ commitment sometimes; some teachers even propose a resignation. Regulations for newly recruited teachers and staffs issued almost every year seem to be evident. The school is seemingly unable to integrate between the high-quality system and the teachers’ welfare and comfort-working. These problems, in turn, cost the school disadvantages, namely the financial problems and the constantly-changing human resource quality stability problems. The This field research with qualitative model utilized phenomenological approach under triangulation data validity. Data were obtained tSDMough observation, interview and documentation. This study aims to analyze the implementations of human resource (SDM) management in the 4.0 industraial revolution era at SD Intis School Yogyakarta. The results of this study are: planning tSDMough quality-assurance analysis in recruitment, selection (files, ability tests tSDMough application and field expertise and interviews), training and development conducted weekly (covering physical and spiritual) semesterly and annually workshops, performance evaluating using my Intis application, compensation and working termination.